Overcoming reform resistance and political implementation of large-scale welfare state reforms - Hans Pitlik; Friedrich Heinemann; Rainer Schweickert (WWWforEurope, 2014)
Long-term beneficial welfare state reforms not only face opposition from powerful insiders and beneficiaries of the system in place. While potential losers from a policy change are often relatively easy to spot, ewll-designed reforms generate mostly diffuse gains, and the potential winners are much more difficult to identify. Moreover, gains from reforms regularly do not accrue immediately but only after a costly adjustment or a frictional re-organisation process. Policy change on a large scale hence occasionally triggers political resistance from politically vocal losers, but sometimes also from prospective winners. Overcoming both the 'rational' and ostensibly 'irrational' obstacles to policy change is thus a core challenge of political reform management. A key message is that important factors for successful change have found too little attention in the literature, compared to technical aspects of reform implementation In that respect, policy bundling and developing economic compensation strategies are important devices to mitigate opposition to reform, However, communication of reform goals, credible political commitment, conformity with fairness norms and moral beliefs, trust formation and social learning play important roles for acceptability of reforms in society.
Keywords: D03; D70; H75; D74; D78; P35; 330; Institutional reforms; Political economy of policy reform; Welfare reform